Organizational and pedagogical model of formation of physical culture of the country’s population: theoretical aspect - Bartnovskaya L.A.; Kravchenko V.M.; Ponomarev V.V. (Theory and Practice of Physical Culture, 2024)
Abstract Objective of the study was to substantiate and develop a theoretical model for the formation of physical culture of the country’s population and test it in practice. Methods and structure of the study. The main research methods in the work were: analysis of scientific and methodological literature on the topic of research, survey, questioning, structuring, systematization, modeling, comparison, graphic analysis, abstraction, interpretation, etc. The system of functioning of physical culture and sports among the population in the Krasnoyarsk Territory was also analyzed. All this as a whole made it possible to adjust and formulate a theoretical model for the formation of physical culture of the population of the Krasnoyarsk Territory, which, after testing, can be designed for all regions of the country. Results and conclusions. An analysis of scientific and methodological literature and a number of sociological studies of physical education and sports of the country’s population showed the following dynamics: in 2019, 40% of the country’s population (58.6 million people) were engaged in physical culture and sports, in 2023 – 53% (70 million people), by 2030 it is planned to increase the number of students to 70% (93 million people). In order to achieve the above indicators, it is necessary to improve the system of physical education and recreational work among the population of the country, namely, to design its content to develop in people a culture of physical culture and sports, and the need for systematic physical exercise.